2021
DOI: 10.12911/22998993/137442
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Co-Digestion of Domestic Sewage Sludge with Food Waste: Incorporating Food Waste as a Co-Substrate under Semi-Continuous Operation

Abstract: Anaerobic co-digestion of domestic sewage sludge with food waste as a substrate for biogas production and as a mean for waste management was conducted. The food waste was incorporated into the bioreactor as a cosubstrate semi-continuously via replacement mode and addition mode of operations in ratios up to 50%. The methane gas yield under the replacement mode of operation ranged from 295 to 1358 ml/gVS added and from 192 to 462 ml/gVS added for the replacement mode of operation and the addition mode of operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In Jordan SS quantities are estimated to reach about 180.7 tons/day by 2022, this amount is equivalent to 65,955.5 tons/year. The natural decomposition of the accumulated sludge in Jordan resulted in emission of about 10 5 ton of CO 2 per year ( Aljbour et al., 2021a ). The current management of SS in Jordan lacks any treatment method except dewatering and air drying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Jordan SS quantities are estimated to reach about 180.7 tons/day by 2022, this amount is equivalent to 65,955.5 tons/year. The natural decomposition of the accumulated sludge in Jordan resulted in emission of about 10 5 ton of CO 2 per year ( Aljbour et al., 2021a ). The current management of SS in Jordan lacks any treatment method except dewatering and air drying.…”
Section: Introductionmentioning
confidence: 99%
“…The SS in 32 wastewater treatment plants (WWTP) out of 34 is stored at the same plants, then transported to the local landfills ( Breulmann et al., 2019 ). This practice can cause serious environmental and economic problems, as well as an adverse effect on public health and safety ( Al-Hamaiedeh, 2010 ; Aljbour et al., 2021a , 2021b ). The high level of pathogens and high possibly concentration of heavy metals in SS, besides the high generation rates, necessitates proper management of this waste ( Agrafioti et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more attention has been paid to SW management in Jordan, focusing on recycling, recovery, and reuse. Therefore, researchers have been funded and conducted studies concerning energy and material recovery from Evaluating the In-site Sorting of Solid Waste in Selected Educational Institutions -A Pilot Study Husam Al-Hamaiedeh 1* , Enam Al-Rafiaha 1 , Omar Al-Khashman 2 , Osama Mohawesh 3 , Ali El Hanandeh 4 SW in Jordan [Aljbour et al, 2021;Al-Hajaya et al, 2021;Al Nawaiseh et al, 2021]. Jaradat and Al-Khashman (2013) evaluated the potential recovery of materials from municipal SW (MSW) in Jordan, Ma'an; they concluded that municipal SW management is still facing many challenges due to insufficient data concerning its quality and characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, more than 95% of the consumed energy in Jordan is being imported from outside the country [3][4][5][6]. The DSS is a heterogeneous biomass characterized by high organic matter content, these biosolids could be a source of clean bioenergy and biofertilizers if they converted thermochemically namely via pyrolysis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%